Comparison of five specific assays for determination of dabigatran plasma concentrations in patients enrolled in the START‐Laboratory Register. (3rd January 2018) - Cini, M.; Legnani, C.; Cosmi, B.; Testa, S.; Dellanoce, C.; Paoletti, O.; Marcucci, R.; Poli, D.; Paniccia, R.; Pengo, V.; Tripodi, A.; Palareti, G.; et al.
Abstract: Introduction: Several specific assays are commercially available to determine dabigatran anticoagulant activity. Aims of this multicenter and multiplatform study were to compare five methods for dabigatran measurement and investigate their performances in the low concentration range. Methods: Dabigatran levels were analyzed in 295 plasma samples from patients enrolled in the START‐Laboratory Register by the following methods using dedicated calibrators and controls: STA‐ECA II (Diagnostica Stago), standard and low range Hemoclot Thrombin Inhibitors (Hyphen BioMed), Direct Thrombin Inhibitor Assay (Instrumentation Laboratory), Direct Thrombin Inhibitor Assay (Siemens), Technoclot DTI (Technoclone). Results: Methods showed variable agreement with the Hemoclot Thrombin Inhibitors assay used as reference test, with modest under‐ or overestimations (Bland‐Altman bias from −17.3 to 4.0 ng/mL). Limits of detection and quantification varied depending on the assay (4‐52 and 7‐82 ng/mL, respectively). Between‐run precision and accuracy were good for all methods for both quality control levels. Assay's repeatability assessed at very low dabigatran concentrations (from 10 to 60 ng/mL) was also acceptable, variability generally increased at lower drug levels. Conclusion: The five dabigatran‐specific assays evaluated in this study provided reliable assessment of dabigatran plasma levels, although showing different performances.